'So called caste': S. N. Balagangadhara, the Ghent School and the Politics of grievance**. Issue 3 (3rd July 2018) - Sutton, Deborah Ruth
Abstract : This article is concerned with the small but coherent lobby of political scholarship that has emerged from a lineage of research supervision which centres on the charisma and ideas of S. N. Balagangadhara, a philosopher from the Centre for the Comparative Science of Cultures (Vergelijkende Cultuurwetenschap) at the University of Ghent. In particular, it examines the deployment of his ideas in a spate of recent scholarly and social media declarations that reject the existence of caste and, by extension, caste discrimination. This scholarship – characterised by circular reasoning, self-referencing and a poverty of rigour – has established a modest, if contentious and poorly reviewed, presence in academic spheres of dissemination. The 'Ghent School' describes a group of scholars who rely conspicuously on Balagangadhara's concept of 'colonial consciousness', a crude derivative of Said's thesis of Orientalism. The Ghent School maintain that all extant scholarship on Hinduism, secularism and caste represents an endurance of colonial distortions that act to defame India as a nation. This politics of affront finds considerable traction in diasporic contexts but has little, if any, resonance when mapped against the far more complex politics of caste in India.